Mathematical modeling applied to the drying kinetics of pitomba bark (Talisia esculenta) (Research, Society and Development, 2020)
The present work aims to determine the centesimal composition of pitomba bark, to perform its drying kinetics in three different drying air temperatures, to adjust mathematical models to experimental data and to evaluate the effect of drying temperature on its centesimal composition. add value to this underutilized product. The peels were submitted to the drying process by performing their kinetics in a fixed air velocity convective dryer (1.5 m.s-1) at 50, 60 and 70 ° C, the empirical mathematical models (Lewis, Handerson and Pabis and Page) were adjusted to the experimental data. In fresh and dehydrated barks, their centesimal composition was determined, with respect to the following parameters: humidity, total solids, ashes, lipids, proteins and carbohydrates. The Page mathematical model was indicated as the best fit due to its high R2 values (R2> 0.99) and the smallest chi-square function values for all applied drying temperatures. Lower moisture and protein values were obtained when higher temperatures were applied. For the total solids, ash and lipid content there was an increase when higher temperatures were applied. The results obtained in relation to the total carbohydrate content were relatively high evidencing that the pitomba bark flour is a high fiber powder.